2013
DOI: 10.1038/srep02783
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing between genotoxic and non-genotoxic hepatocarcinogens by gene expression profiling and bioinformatic pathway analysis

Abstract: A rapid and sensitive method to determine the characteristics of carcinogens is needed. In this study, we used a microarray-based genomics approach, with a short-term in vivo model, in combination with insights from statistical and mechanistic analyses to determine the characteristics of carcinogens. Carcinogens were evaluated based on the different mechanisms involved in the responses to genotoxic carcinogens and non-genotoxic carcinogens. Gene profiling was performed at two time points after treatment with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 35 publications
4
33
0
Order By: Relevance
“…This is in line with previous findings, where similar biological functions have been shown to be affected by genotoxic compounds in vitro; e.g. see Lee et al (), Magkoufopoulou et al (), Mathijs et al (), and Smit et al ().…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with previous findings, where similar biological functions have been shown to be affected by genotoxic compounds in vitro; e.g. see Lee et al (), Magkoufopoulou et al (), Mathijs et al (), and Smit et al ().…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the induction of HCC was accompanied by a significant decrease in the total body weight and deterioration of the liver functions as well as an elevation of AFP tumour marker in the animals treated with DENA. These findings can be explained by the fact that, DENA is a well‐known genotoxic hepatocarcinogen which induce an energy‐wasting syndrome known as cancer cachexia . Additionally, our results showed that prolonged DENA administration caused a redox imbalance.…”
Section: Discussionsupporting
confidence: 56%
“…This confirms that p53 is a universal sensor of DNA damage in human cells [8] and that measurement of p53 TG transcriptional induction is a relevant approach to monitor all types of DNA damage occurring in human cells. Transcriptomic-based assays had previously been developed to evaluate genotoxic activity of chemicals [18]. By selecting a limited number of p53 TGs, we then derived a simple and rapid assay based on RT-QMPSF analysis of the p53 TGs induction in The numbers indicate the number of genes induced more than twice in wild-type TP53 EBV-immortalized lymphocytes exposed to the drugs at concentrations indicated in Table 1, for 16 h, as determined using Whole Human Genome Oligo 4 × 44 K Microarray (G4845A, Agilent) and the Agilent Two-Color Gene Expression workflow.…”
Section: Discussionmentioning
confidence: 99%